2018
DOI: 10.1103/physrevb.98.184414
|View full text |Cite
|
Sign up to set email alerts
|

Unusual rotating magnetocaloric effect in the hexagonal ErMnO3 single crystal

Abstract: It is known that orthorhombic RMnO3 multiferroics (R = magnetic rare earth) with low symmetry exhibit a large rotating magnetocaloric effect because of their strong magnetocrystalline anisotropy. In this paper, we demonstrate that the hexagonal ErMnO3 single crystals also unveils a giant rotating magnetocaloric effect that can be obtained by spinning them in constant magnetic fields around their a or b axes. When the ErMnO3 crystal is rotated with the magnetic field initially parallel to the c-axis, the result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 69 publications
(196 reference statements)
0
17
0
Order By: Relevance
“…Similarly to the standard MCE, the isothermal entropy change associated with the rotation of TbVO4 single crystals between two different crystallographic directions can be also determined from magnetic isotherms. Considering the magnetic field initially applied along the c direction, the obtained rotating magnetocaloric effect (RMCE) in term of ΔST when spinning the crystals between the hard and easy axes by an angle of 90 ° in a constant magnetic field H is simply given by [1,14,[16][17][18]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to the standard MCE, the isothermal entropy change associated with the rotation of TbVO4 single crystals between two different crystallographic directions can be also determined from magnetic isotherms. Considering the magnetic field initially applied along the c direction, the obtained rotating magnetocaloric effect (RMCE) in term of ΔST when spinning the crystals between the hard and easy axes by an angle of 90 ° in a constant magnetic field H is simply given by [1,14,[16][17][18]:…”
Section: Resultsmentioning
confidence: 99%
“…The latter have used the magnetocaloric garnet Dy2.4Gd0.6Al5O12 as refrigerant, resulting in the decrease of the hydrogen temperature at the cold side down to 20 K. However, the large specific heat usually shown by the garnet compounds 3 lower drastically their MCE in term of the adiabatic temperature change that reaches only 1 to 2 K in the magnetic field change of 1 T [8,9]. In order to deal with these drawbacks, interesting materials with better magnetocaloric performance in the temperature range below 30 K were recently reported including both intermetallics [10][11][12][13] and oxides such as RMO3 (M = metal) [14][15][16][17][18][19][20][21]. On the other hand, the RMn2O5 multiferroics are also of great importance in the cryogenic temperature range not only because of their strong MCEs that are usually obtained by varying magnetic fields along their easy-axes, but also due to their strong magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The application of magnetocrystalline anisotropy is the rotating magnetocaloric effect. [8][9][10][11][12][13][14] The temperature and heat exchange of the anisotropic magnetic material can be controlled by rotating the sample (or changing the relative direction of the external magnetic field) at a fixed strength of the applied magnetic field. The origin of this effect is the modification of the magnetocrystalline anisotropy on the magnetization when changing the relative direction of the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…However, several experimental studies have found that the isothermal magnetic entropy change is modified not only on the low-temperature side but also on the high-temperature side of the main peak when a magnetic field is applied in different directions. [8][9][10][11][12][13][14] The magnetocrystalline anisotropy energy affects the isothermal magnetic entropy change even above the Curie temperature in the anisotropic magnetocaloric effect.…”
Section: Introductionmentioning
confidence: 99%